A Study on Farmwomen Training Preference on Farm Implements - Gupta, Shobhana; Verma, Shilpi (Indian Journal of Extension Education, 2016)
The study was aimed at determining women farmers' perception about importance, adequacy and need of training in farm  implements. A sample size of 240 women farmers was taken for the study and analyzed. Simple random sampling  technique was used for the sample selection and structured questionnaire was used to elicit information from the  respondents. Both descriptive and inferential statistics were used for data analysis. The result showed highest information  about the repair of pump sets, oil engine; electric motor etc. was most important and most needed. Exposure to the use of  farm implements was perceived as most adequate. It can be inferred that the rural women are in need of training in  majority of the areas in farm implements. Hence, there is a wide scope for the extension workers to organize and impart  training to farm women in order to enhance their potential in adoption of improved technologies. Therefore, providing  appropriate training in the area of farm implements to rural women will enable them in the updating their knowledge and  enhancing in the skills.
Keywords: Training; farm women; farm implements; farming practices